Improving Performance of Coleus through Mutation Induction by Gamma Ray Irradiation - Aisyah, Syarifah Iis; Marthin, Yodi; Damanik, M. Rizal M. (Department of Agronomy and Horticulture, IPB University, 2015)
The objective of this study is to study the effect of gamma ray irradiation (15, 30, 45, and 60 gray (Gy) to determine Lethal Dose 50 (LD50) values, and to obtain new Coleus variances in a relatively short time. The study was conducted in a greenhouse at Cikabayan experimental field, Bogor Agricultural University, Darmaga, Bogor in May to July 2013. Gamma irradiation treatment significantly affected height, number of leaves, and number of nodes. Increasing the dose level of gamma irradiation tend to inhibit plant growth. LD50 for yellow/green, green/brown, variegated green/brown of Coleus blumei, and Coleus amboinicus Lour were 48.66, 65.2, 52.81, and 37.62 Gy respectively. C. amboinicus irradiated at a dose level of 45 Gy had different leaf shapes compared to control. Keywords: Coleus, gamma ray irradiation, LD50 values, ornamental plant, torbangun